PATTERN OF ANTICOAGULANT THERAPY IN CARDIOEMBOLIC STROKE - Reihan Achmad Reza; Lisda Amalia; Nushrotul Lailiyya Dahlan; Cep Juli; Hanna Goenawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Cardioembolic stroke is a category of ischemic stroke that manifests more severe, is prone to recurrence, and is related to a higher mortality rate than the other categories of ischemic stroke. Anticoagulant therapy is recommended in cardioembolic stroke, both for primary and secondary prevention. Objective: The objective of this study is to understand the pattern of anticoagulant therapy in cardioembolic stroke patients admitted at Hasan Sadikin General Hospital Bandung. Methods: The methodology of this study uses retrospective descriptive cross-sectional and use data from medical records collected during January 2015 to December 2020 at Neurology Department of Hasan Sadikin General Hospital with total sampling method. The inclusion criteria were cardioembolic stroke patients that received anticoagulant therapy. Anticoagulant therapy was stratified into Warfarin and New Oral Anticoagulants (NOACs) which consist of dabigatran, rivaroxaban, and edoxaban. To assess stroke severity outcome between warfarin and NOACs we use the National Institutes of Health Stroke Scale (NIHSS) Score. Results: From the 162 cardioembolic stroke patients, the most common oral anticoagulant used was warfarin (90.12%), followed by dabigatran (4.94%), rivaroxaban (3.70%), and edoxaban (1.23%). Only 1 (0.62%) patient who experienced complications from anticoagulant therapy, the complication was non-major bleeding and occurred in warfarin users. Both warfarin and NOACs mainly had NIHSS on discharge in a moderate category with the mean of NIHSS 7.615 and 7.276 for warfarin and NOACs respectively. Conclusion: Warfarin is the most common oral anticoagulant used for cardioembolic stroke based on this study. Both warfarin and NOACs groups have similar stroke severity outcomes measured by NIHSS on discharge and NOACs have lower incidence of bleeding compared to warfarin group.